Animal genetic resources in Africa. High potential and endangered livestock (1985)
Discusses the FAO/UNEP programme on animal genetic resources conservation and management; and the indigenous breeds identified as of high potentials in the different ecological zones of Africa. The different activities of ILCA's Documentation Centre and the range of information service it provides to its users are explained. Report on the FAO consultation on data bank establishment in Africa included.